Examining gaps in mathematics achievement among racial-ethnic groups, 1972-1992 - Berends, Mark, 1962- (RAND Corporation, 2005)
As schools in the United States become more output driven, students, educators, administrators, and policymakers are being held accountable for improving the academic achievement of all students. Federal education policy now mandates that states, districts, and schools monitor achievement gaps among students of different socioeconomic, racial-ethnic, and language groups. This book examines several nationally representative senior high school student cohorts between the early 1970s to early 1990s to understand trends in the mathematics scores of these different racial-ethnic groups, and analyzes how changes in family, school, and schooling measures help explain changes in the test score gaps over time. The authors find that there were positive changes in some socioeconomic family background characteristics for black and Latino students, helping them narrow the gap with white students. Moreover, although there were few positive changes between schools, the within-school experiences of black and Latino students changed for the better compared with white students when measured by student self-reported academic track placement. Despite some beneficial changes for black and Latino students, inequalities persist. The authors point out the possibilities of various policies that address improving the socioeconomic and educational opportunities of students. Policymakers should think in more creative, coordinated, and comprehensive ways if the nation is to more effectively address student achievement gaps.